Development and Prototyping of Jet Systems for Advanced Turbomachinery with Mesh Rotor - Yuri Appolonievich Sazonov; Mikhail Albertovich Mokhov; Inna Vladimirovna Gryaznova; Victoria Vasilievna Voronova; Khoren Arturovich Tumanyan; Mikhail Alexandrovich Frankov; Nikolay Nikolaevich Balaka (Emerging Science Journal, 2021)
This article presents the research results that aim to develop promising mesh turbomachines equipped with jet control systems. The turbomachines operating in difficult conditions in oil and gas production are mainly considered. At the same time, some research results can be used in other production branches, including power engineering and transport. Three-dimensional models for computer simulation of net turbines and jet control systems were developed. Prototypes and micromodels were created to test the performance of mesh turbines and jet control systems using additive technologies. A methodological approach is proposed to create a classification of jet control systems considering their design and technological features. In the course of numerical experiments, the extreme conditions of fluid and gas outflow through a nozzle equipped with a velocity vector control system, in the control range of adjustment of the velocity vector deflection angle from + 90o to -90o within a geometric hemisphere, have been considered for the first time. It was also shown that when using a dual-channel nozzle, there are possibilities to adjust the velocity vector angle (thrust vector) in the range of + 180o to -180owithin the geometric sphere. Compared with the known variants, the control range of the velocity vector angle is increased by nine times. These calculated data are presented in addition to the previously published results of physical laboratory experiments. Preliminary results of numerical experiments show the possibility of creating a new theory in the field of mesh turbines and jet systems. Patents support the novelty of the developed technical solutions. Doi: 10.28991/esj-2021-01311 Full Text: PDF